(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2017)
This article presents assessment techniques attitude domain based on the curriculum 2013, especially the subjects of Islamic Religious Education and moral value (PAI BP) elementary level. This due to the demands i n assessment implementation among attitude, knowledge and skill domains must be in a balance. In 2013, four elements of the National Education Standards 1) Graduate Competency Standards, 2) Content Standards, 3) Process Standards, and 4) Evaluation Standards were revised. Assessment is an effort to collect and process the data of the learning process to determine the level of achievement of the competence of the learners as the basis of the follow-up decision of an educator. While the attitude assessment is an assessment conducted by the teacher to measure the l evel of attai nment of atti tudinal competencies of learners that include aspects of receiving or paying attention, responding, assessing or appreciating, organizing and managing,. There are 3 ways to assess the domain of attitude that is through observation, sel f-assessment, and among friends. Observations are conducted during the process and outside the learning process, while self-assessment and between friends is done at least once a semester. Many of the difficulties experienced by teachers in the implementation ranging from the preparation of rubric, implementation and the final processing technique.